2019
DOI: 10.5089/9781498303996.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy Multipliers in Small States

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management. AbstractGovernment debt in many small states has risen beyond sustainable levels and some governments are considering fiscal consolidation. This paper estimates fiscal policy multipliers for small states using two distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…Perhaps the most striking difference in estimates corresponds to public consumption, with the multipliers from the one-stage approach being much lower than the two-stage estimation. This is in line with, for example, lower multiplier estimates obtained by Alichi et al (2019), Honda, Miyamoto and Taniguchi (2020) or Cacciatore et al (2021), that estimate multipliers using similar one-stage procedures 25 . This shows that results in the literature are in line to what we find if we were using a similar methodology.…”
Section: One-stage Vs Two-stage Estimationsupporting
confidence: 86%
“…Perhaps the most striking difference in estimates corresponds to public consumption, with the multipliers from the one-stage approach being much lower than the two-stage estimation. This is in line with, for example, lower multiplier estimates obtained by Alichi et al (2019), Honda, Miyamoto and Taniguchi (2020) or Cacciatore et al (2021), that estimate multipliers using similar one-stage procedures 25 . This shows that results in the literature are in line to what we find if we were using a similar methodology.…”
Section: One-stage Vs Two-stage Estimationsupporting
confidence: 86%
“…Several follow-up papers, including Edelberg et al (1999) and Burnside et al (2004), embedded these 'war dates' in VARs, with the narrative series ordered first in a Cholesky decomposition, creating so-called expectations-augmented VARs (or EVARs). 6 EVARs have been expanded to include other measures of expectations, such as forecast errors of professional and/or public sector forecasters, in order to account for the predictable and/or anticipated element of government spending; examples include Auerbach and Gorodnichenko (2012) and Alichi et al (2019), among others. Most of these narrative-based studies found that shocks to government spending (as proxied by changes in military spending) led to increases in GDP and hours worked, at least in the short run, but that it lowered private consumption and investment.…”
Section: Government Spending Shocksmentioning
confidence: 99%
“…In a survey of the literature, Ramey (2016) found that most estimates of the government spending multiplier in the developed world vary between 0.6 and 1.5. Much less evidence is available for the developing world, but the scarce empirical literature suggests that multipliers are smaller in emerging-and low-income economies (see, for example, Alichi et al 2019;Batini et al 2014;Estev ao and Samaké 2013;Gnip 2014;Ilzetzki 2011;Ilzetzki et al 2013;IMF 2008;Kraay 2012). Empirical research into spending multipliers for South Africa is even more scarce.…”
Section: Government Spending Shocksmentioning
confidence: 99%
“…The emerging literature on fiscal multipliers strongly suggests that public investment has a significant positive impact on economic growth, both in the high income and in developing countries (see Leeper et al, 2010;Ilzetzki et al, 2013;Eden and Kraay, 2014;Alichi et al, 2019). Many of these studies also indicate that fiscal multipliers associated with public investment are significantly higher than multipliers associated with current expenditures (Ilzetzki et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public investment yields a double dividend in terms of economic growth and a decrease in unemployment, as it provides a positive impetus both during its implementation (boosting demand) and after completion (encouraging supply, by reducing the costs and risks of private investment). Many empirical studies show that fiscal multipliers of public investment are rather high, not only in large economies but also in small economies, thus outperforming multipliers of current expenditures (Ilzetzki, 2013;Alichi, 2019).…”
Section: Introductionmentioning
confidence: 99%